GAMBARAN FAKTOR RISIKO PADA KEJADIAN MORTALITAS PASIEN STEMI DI RSUD ULIN BANJARMASIN - Dewi, Ridha Fahliati; Wahid, Abdurahman; Hafifah, Ifa (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2016)
This incidence rate of STEMI patients followed by risk factors that affect prognosis of STEMIpatients, there’s a need to acknowledge what risk factors that role in STEMI as prevention todecrease mortality incidence. The objectives was to describe risk factors of mortality incidence inSTEMI patients in RSUD Ulin Banjarmasin. This study used cross sectional with accidentalsampling method that showed through univariate analysis. The data taken from ECG sheet,patient and family interviewed, nurse and doctor declaration written on medical record thatbeing record directly by researcher on observational sheet in RSUD Ulin Banjarmasin sinceNovember - December 2015. The results17 patients having STEMI with mortality rate (11,8%)average age STEMI patients is 57 years old, dominated by males (88,2%) with risk factors arehistory of prior heart (35,5%), hypertension (29,4%), smoking (29,4%), stroke (5,9%), nomedical history (17,6%). The result of this study was avarege age of STEMI patients in RSUDUlin Banjarmasin was 57 years old and the most common in males with risk factors were historyof prior heart, hypertension, smoking, stroke and no medical history.